Professional Preferences of Translators/Interpreters-to-be: Survey Results - Elena Makeeva; Marina Kulinich; Ekaterina Savitskaya (ARPHA Proceedings, 2020)
In the former Soviet Union translators/interpreters-to-be were trained only in a few field-specific linguistic (and in a couple of military institutions. Later, in XXI, Russia signed the Bologna Declaration, Russian institutes and universities got an opportunity to choose what they teach, were allowed to provide commercial services and many introduced both short-term training courses for translators/interpreters and long-term BA / MA translator training programs as the social demand for translators increased. This paper discusses various ways and means of translator/interpreter training both in Russia and abroad together with those practiced in Samara State University of Social Sciences and Education. The paper also presents the results of regular anonymous questionnaires among the students dealing with links between our teaching and students’ views in order to facilitate both students’ professional training and to make the curriculum more adaptive to the present-day situation on the job market.The results showed that though most students’ views on their future profession are rather vague, most of them are not disappointed in the profession chosen. Bachelors' and masters' attitudes and assessments, however, differ as senior students have more experience and can critically evaluate their future career perspectives. Master students value their university and practical experience more than bachelor students, they know more of the situation in the job market and are ready to face the challengers of this profession. The authors conclude that the existing BA / MA programs need changes considering both students’ and their potential employers’ interests and demands.